2008
DOI: 10.1021/jo8023544
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of α-Chloroaldoxime O-Methanesulfonates and Their Use in the Synthesis of Functionalized Benzimidazoles

Abstract: Three different alpha-chloroaldoxime O-methanesulfonates were synthesized to investigate their chemical properties. The compounds were found to be stable and were able to be stored at ambient temperature without any precautions. The reactions with anilines were investigated, and it was found that an additive is required to activate the sulfonate. TMEDA was found to be the most efficient additive, and various benzimidazoles were synthesized through the reaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…Benzimidazoles and 2‐aminobenzimidazoles are very powerful compounds because of their applications in therapeutic and biological sciences (Figure ) . These compounds were used as neuropeptide YY1 receptor antagonist, N ‐methyl‐D‐aspartate (NMDA) antagonist, factor Xa(FXa) inhibitor, poly(ADP‐ribose)polymerase (PARP) inhibitor and non‐peptide thrombin inhibitor .…”
Section: Figurementioning
confidence: 99%
“…Benzimidazoles and 2‐aminobenzimidazoles are very powerful compounds because of their applications in therapeutic and biological sciences (Figure ) . These compounds were used as neuropeptide YY1 receptor antagonist, N ‐methyl‐D‐aspartate (NMDA) antagonist, factor Xa(FXa) inhibitor, poly(ADP‐ribose)polymerase (PARP) inhibitor and non‐peptide thrombin inhibitor .…”
Section: Figurementioning
confidence: 99%
“… Their later report indicated that the cyclization was more conveniently carried out by a coupling reaction between an aniline and O -mesyl-α-chloroaldoxime 17 followed by annulation in the presence of N , N , N ′, N ′-tetramethylethylenediamine (TMEDA) in an one-pot reaction manner (eq 2 in Scheme ). In addition, the group established a convenient method to prepare substrate 17 by a sequence of N -chlorosuccinimide (NCS)-based α-chlorination of an aldoxime and a subsequent mesylation. By these methods, a variety of benzimidazoles 19 were prepared.…”
Section: Anilinesmentioning
confidence: 99%
“…The mixture was heated to reflux for 16 h, cooled to room temperature, and filtered through a pad of Celite which was washed well with ethyl acetate. The filtrate was concentrated in vacuo, and the residue was purified by flash column chromatography (SiO 2 , 1:1, hexane/ethyl acetate) to provide 19 as an orange solid (81 mg, 39%): 31 2,6-Bis[(4R,5R)-4,5-Dihydro-4,5-diphenyl-1H-imidazol-2-yl]pyridine (20). Cesium carbonate (85 mg, 0.26 mmol), anhydrous toluene (1 mL), 2,6-dibromopyridine (47.4 mg, 0.2 mmol), tert-butyl isocyanide (68 μL, 0.6 mmol), (1R,2R)-(+)-1,2-diphenylethylenediamine (425 mg, 2.0 mmol), palladium(II) chloride (1.8 mg, 0.01 mmol), and dppp (8.2 mg, 0.02 mmol) were added to an oven-dried, three-necked flask under nitrogen.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%